Unexpected discovery of a new Lycocerus (Coleoptera, Cantharidae) from Okinawa Island, Ryukyu Islands, southwest Japan - Nakamura, Ryo (Zootaxa, 2024)
The soldier beetle fauna of East Asia is very diverse, and despite the long-term tradition of taxonomic research, it remains incompletely known. A new soldier beetle species Lycocerus todai Nakamura sp. nov. is described from Okinawa Island (Ryukyu Islands, southwest Japan). The discovery of L. todai sp. nov. not only marks an unexpected addition to the well-studied Japanese Lycocerus, but also unveils significant biodiversity in the Ryukyu Islands. Two similar species from the same island, L. okinawanus (Ishida, 1985) and L. yonaensis (Satô et Okushima, 1992), are also examined and a the distribution map of all three species is provided.